ON THE DESIGN OPERATION AND EFFICIENCY OF IIM DUAL PURPOSE TRAWL FOR SAMLL MACHANISED BOATS - KARTHA, K N; SADANANDAK, K A (Fishery Technology, 2016)
Preliminary midwatcr fishing trials were conducted off Cochin with a 11 m. dual purpose trawl during the monsoon months when the prawns were available in the column layers. Further, with a view to assess its suitability as bottom trawl, the gear with suitable modifications in the rigging was towed in comparison with a 15m. bottom trawl along the depth ranges of 5-10 m. and 10-20 m. and the fishing operations were found satisfactory